P-BN45 The Impact of Covid-19 on Benign Upper GI Operations in England During 2020. (16th December 2021) - Sandland-Taylor, Laura; Jenkins, Barbara; Beckingham, Ian
Abstract: Background: Since the cancellation of elective surgery in early 2020 due to the threat of Covid-19, surgical provisions in England have continued to be affected by the Covid-19 pandemic. Elective surgery makes up the majority of surgical procedures performed in England and therefore   cancelled operation lists and increased demand for ITU beds has had a significant impact upon the surgical services delivered to patients through out 2020. The following research looks at the impact of Covid-19 on benign upper GI surgery in England and reviews the relationship between Covid-19 deaths and operations performed throughout England and analyses the data at a regional level.  Methods: Data relating to operation numbers was taken from The Surgical Workload Outcomes Audit (SWORD) database. The SWORD database was interrogated for the years 2017 – 2020. A mean number of operations was calculated using the 2017-2019 data and compared to data from 2020. Operations performed and other demographic data  was analysed regionally and compared to Covid-19 deaths throughout England. Covid-19 data was obtained from the national government dashboards.  Results: The results show that there is a correlation with increasing Covid deaths and lower rates of elective surgery. Furthermore, elective surgery was worse hit than emergency surgery with a slower recovery overall. Cholecystectomies were reduced by a total of 20817 (31.4%) for the year 2020 with a greater reduction seen in elective operations (35.6%). However, similar reductions were seen in both laparoscopic (31.4%) and open (37.5%) Similarly, bile duct explorations and elective splenectomy were reduced by 34.4% and 23.4% respectively. Comparatively, both paraumbilical and inguinal hernias also saw reductions of greater than 40% in 2020 when compared to the mean of the previous 3 years. Regional variances were seen between operation numbers performed and Covid-19 rates, however the overall trend remained the same for national level data.  Conclusions: Overall, the Covid-19 pandemic has had a significant impact on operations, particularly on those deemed as benign and 'less urgent'. Whilst a global impact across all benign operations was seen, greater reductions were seen in elective operations compared to emergency operations. Hernia operations and bile duct exploration saw greater overall reductions compared to cholecystectomies and splenectomies, which suggests that whilst operation numbers were reduced, efforts were made to prioritise operations with greater clinical need throughout the pandemic. On analysis of the data in relation to Covid-19 rates and deaths, variation was seen across the regions in the UK, however overall the trend remained the same. Centres and regions worse hit by Covid-19 performed less operations during 2020. However, further qualitative research to investigate why certain centres maintained higher levels of performance during the pandemic would be beneficial for planning for future waves and future pandemics.